2019
DOI: 10.1039/c9nr01922g
|View full text |Cite
|
Sign up to set email alerts
|

Bromine polycondensation in pristine and fluorinated graphitic carbons

Abstract: We reveal two distinct intercalated bromine species and propose bromination mechanisms of fluorinated carbons depending on the fluorination level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 62 publications
(95 reference statements)
3
9
0
Order By: Relevance
“…At this fluorine content, the sp 2 -hybridized regions consist of several fused carbon hexagons surrounded by CF groups. According to DFT calculations, bromine molecules move over the surface of a graphene nanoregion to the CF border and spontaneously interact there to form Br 3 –Br 3 chains . The vibrations in such chains are in good agreement with the experimental values observed in the Raman spectra.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…At this fluorine content, the sp 2 -hybridized regions consist of several fused carbon hexagons surrounded by CF groups. According to DFT calculations, bromine molecules move over the surface of a graphene nanoregion to the CF border and spontaneously interact there to form Br 3 –Br 3 chains . The vibrations in such chains are in good agreement with the experimental values observed in the Raman spectra.…”
Section: Introductionsupporting
confidence: 73%
“…Polybromide chains were detected by X-ray diffraction (XRD) studies of stage-2 bromine–graphite intercalants; the Raman spectra of such compounds showed at least two components of the Br–Br vibrations. Interestingly, a similar complex shape of the bromine band was observed in the Raman spectra of bromine-FGICs when the fluorine content x was below 0.5 in the C 2 F x layers . At this fluorine content, the sp 2 -hybridized regions consist of several fused carbon hexagons surrounded by CF groups.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…For ICl-C 9.8 GIC, a similar structure with an AαAβ stacking order is proposed. Structural elucidation is challenging based solely on experimental data; thus, density functional theory (DFT) calculations were performed using the AIMPRO package, an approach previously successfully applied to other halogenated nanocarbons. , We address the choice of exchange–correlation functional and dispersion description further in the Supporting Information, including benchmarking methods to experimentally measurable quantities (see also the Supporting Information). Different ICl structures were examined in both graphite and graphene systems, all of which show exothermic binding compared to isolated ICl.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the Raman spectrum of brominated samples exhibited a peak at 153 cm 1 , attributed to polybromine Br n chains [45,48]. Our recent calculations have shown the chains are mainly composed of the Br 3 based species [49]. Bromine related peaks overlap with RBMs from the outer nanotubes, which does not allow revealing changes in their electronic structure as the result of bromination.…”
Section: Instrumentationmentioning
confidence: 90%